The Usborne book of the earth (London : Usborne Pub, 1992)
Contents.--Planet earth / Fiona Watt.--Ecology / Richard Spurgeon.--Energy & power / Ricahrd Spurgeon and Mike Flood.--Weather & climate / Fiona Watt and Francis Wilson.
Includes glossaries and index.
Keywords: Earth -- Juvenile literature; Ecology -- Juvenile literature; Force and energy -- Juvenile literature; Power (Mechanics) -- Juvenile literature; Weather -- Juvenile literature; Climate -- Juvenile literature